Home-Work Postcolonialism, Pedagogy, and Canadian Literature - Sugars, Cynthia (Reappraisals: Canadian Writers, 2004)
Canadian literature, and specifically the teaching of Canadian literature, has emerged from a colonial duty to a nationalist enterprise and into the current territory of postcolonialism. From practical discussions related to specific texts, to more theoretical discussions about pedagogical practice regarding issues of nationalism and identity, Home-Work constitutes a major investigation and reassessment of the influence of postcolonial theory on Canadian literary pedagogy from some of the top scholars in the field.